2021
DOI: 10.1002/cem.3339
|View full text |Cite
|
Sign up to set email alerts
|

Chemometry‐assisted UV‐spectrophotmetric methods for the simultaneous determination of paritaprevir, ritonavir, and ombitasvir in their combined tablet dosage forms: A comparative study

Abstract: The ternary mixture under study is a recent hepatitis‐C antiviral medicine composed of three new directly acting antiviral drugs, namely, ombitasvir, paritaprevir, and ritonavir. They are co‐formulated as a single‐dose combined tablet dosage form. With more than 170 million infected patients worldwide, a large production scales of antivirals medicine is expected, and hence, new simple and fast methodologies are required to cover millions of analyses that are done routinely in the different pharmaceutical quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Univariate calibration methods could not resolve this severe spectral similarity and overlap. Multivariate models are useful in complex spectral analysis due to the inclusion of many spectral wavelengths instead of a single one, resulting in an improvement in the predictive ability and precision of the models [33]. Thus, five multivariate multi-level chemometric models (CLS, PCR, PLS, GA-PLS, and ANN) were useful in this mixture resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Univariate calibration methods could not resolve this severe spectral similarity and overlap. Multivariate models are useful in complex spectral analysis due to the inclusion of many spectral wavelengths instead of a single one, resulting in an improvement in the predictive ability and precision of the models [33]. Thus, five multivariate multi-level chemometric models (CLS, PCR, PLS, GA-PLS, and ANN) were useful in this mixture resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Being all orally active drugs, their combination is predicted. Although several research articles were reported for determination of FVR in plasma [16][17][18][19][20], or in pharmaceutical dosage forms [7,[21][22][23][24], and also for determination of RTV [10,[25][26][27][28], only two LC-MS/MS methods were reported for MLP determination in human plasma [29,30] and one paper was reported for determination of MLP and FVR simultaneously [31]. Most of such chromatographic techniques, especially those coupled with MS, are expensive and requires highly qualified personnel [32].…”
Section: Introductionmentioning
confidence: 99%
“…Although UV-Spectrophotometry is a rapid, sensitive, and inexpensive technique for analysis, it is difficult to apply direct UV-Spectrophotometric techniques to the examination of binary pharmaceutical formulations, owing to spectrum overlap and a lack of specificity. Today, new spectrophotometric techniques that use simple software and math are used to separate overlapping spectra [ 21 ].…”
Section: Introductionmentioning
confidence: 99%